Rodna ravnopravnost u visokoškolskom obrazovanju: horizontalna rodna segregacija u području društvenih nauka / Gender Equality in Higher Education: Horizontal Gender Segregation in the Social Sciences - Ždralović, Amila (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
Gender equality is a crucial issue for the 21st century society, which implies the responsibility of universities to critically review the current situation, identify social circumstances in which education takes place, and creatively design ways in which they can change social reality. Considering the imperatives of gender-inclusive education, this research is focused on the problem of horizontal gender segregation and its reflection on vertical segregation. The examination starts with insight into the general situation in higher education institutions in BiH to pay special attention to the field of social sciences at the University of Sarajevo. Based on the meta-analysis of available secondary data, the analysis primarily determines the 'diversity index' in this area, and identifies the specifics of scientific fields and the differences between them.